ВИЗНАЧЕННЯ ВІДСТАНІ ДО МІСЦЬ ОДНОФАЗНИХ ЗАМИКАНЬ НА ПОВІТРЯНИХ ЛІНІЯХ - Гребченко, М.В.; Максимчук, В.Ф.; Пилипенко, Ю.В. (Інститут електродинаміки НАН України, Київ, 2016)
Results of developing a method of determining the distance to the phase-to-ground and the resistance value in the place of circuit overhead lines in networks with isolated unbranched her trawls. The method is based on the ratio of the voltage drop on the plot line phase voltage and phase-circuit between the point and the ground. This takes account of the current vector, which runs through the site closure. In the practice of the method between each phase and earth are containers that are automatically disabled when a phase-to-ground. Mathematical modeling and industrial loopback test. References 6, figures 3.